Relationship Between Patient-Reported Assessment of Shoulder Function and Objective Range-of-Motion Measurements. (1st March 2017) - Matsen, Frederick A.; Tang, Anna; Russ, Stacy M.; Hsu, Jason E.
Abstract : Background: Assessment of function is the cornerstone of clinical shoulder research. This purpose of this study was to answer 3 relevant questions: How does subjective patient assessment of shoulder function correlate with objectively measured active shoulder range of motion? What is the difference in active motion between shoulders that can and those that cannot be used to perform each of the functions of the Simple Shoulder Test (SST)? Does the relationship between subjective and objective assessment of shoulder function differ between male and female patients? Methods: We analyzed the relationship between objective range-of-motion measurements recorded by the observer-independent Kinect motion capture system and SST patient self-assessments of shoulder function of 74 male and 30 female patients with osteoarthritis. Results: There was poor correlation between objective measurements of active abduction and total SST scores of osteoarthritic shoulders of patients seen before shoulder surgery: the coefficients of determination (R 2 ) were 0.29 for the osteoarthritic shoulders of women and 0.25 for those of men. The relationships between active abduction and total SST score were closer for the contralateral shoulders (R 2 = 0.54 for women and R 2 = 0.46 for men). The difference in active abduction between the osteoarthritic shoulders that allowed and those that did not allow the patient to perform the individual SST functions was significant (p < 0.05) for only 4 of the 12 functions in the female group and 5 of 12 in the male group because of the highly variable relationship between self-assessed function and active abduction. In contrast, when the contralateral shoulders were assessed, this difference was found to be significant for 10 of the 12 functions in the female group and all 12 of the functions in the male group. The relationship between objective motion and subjective function did not differ significantly between male and female subjects. Conclusions: The self-assessed function of osteoarthritic shoulders of women and men is only partially determined by the active range of abduction. Both subjective and objective measurements are important in characterizing the clinical status of shoulders. Studies of treatment outcomes should include separate assessments of these 2 complementary aspects of shoulder function. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.